Effectiveness of Play-Based Learning Strategy in Teaching Filipino for Grade Two Pupils - Dela Cruz, Noemi Ruth (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the effectiveness of a play-based learning strategy in teaching Filipino among Grade Two pupils at Pagkalinawan Elementary School, Jalajala Sub-Office, Division of Rizal, during the School Year 2025–2026. Anchored on child-centered and experiential learning principles, the research employed an experimental method utilizing a parallel group design. Two sections of Grade Two pupils participated in the study: nineteen (19) pupils in the experimental group were exposed to play-based learning strategies, while twenty (20) pupils in the control group were taught using the traditional method. Respondents were described according to sex, sibling position, number of children in the family, monthly family income, parents’ educational attainment, and parents’ occupation. Pretest and posttest assessments were administered to both groups to measure their level of performance in Filipino.Findings revealed that both groups demonstrated a Fairly Satisfactory level of performance in the pretest. After the intervention, the experimental group achieved a Very Satisfactory level, while the control group attained a Satisfactory level in the posttest. Statistical analysis showed significant improvements within both groups based on pretest and posttest results. Moreover, a significant difference was found between the posttest performances of pupils exposed to play-based learning and those taught through the traditional approach, favoring the experimental group. However, no significant differences were noted in pupils’ performance when grouped according to their personal and family-related characteristics.The study concluded that play-based learning is an effective strategy in improving the Filipino language competencies of Grade Two pupils. Although both instructional approaches led to performance gains, play-based learning yielded higher achievement outcomes. It is recommended that teachers continuously integrate play-based and other interactive strategies in Filipino instruction, collaborate with parents to reinforce learning at home, and implement the proposed action plan. Further parallel studies considering additional variables are likewise encouraged.